Combined effects of elevated temperatures and high strain rates on compressive performance of S30408 austenitic stainless steel. (December 2021) - Li, Lijun; Wang, Rui; Zhao, Hui; Zhang, Haoran; Yan, Rui
Abstract: This paper presents an experimental investigation on the dynamic mechanical performance of S30408 austenitic stainless steel (ASS) under elevated temperatures, which is essential for determining the behaviour of structures made with this type of steel subjected to the coupled fire and impact/explosion. For this purpose, the quasi-static and dynamic compression tests using Split Hopkinson Pressure Bar (SHPB) were conducted under temperatures of 20–600 °C and strain rates from 0.001 to 3000 s −1 . In addition, the corresponding microstructures of tested samples were observed. The stress–strain responses, strain rate and temperature effects as well as the microstructural evolutions were analyzed. Test results show that the stress–strain responses are sensitive to the strain rate and temperature. The strain-rate sensitivity coefficient increases as the strain rate and temperature rise. The microstructural observation reveals that the grain dimension declines with an increment of strain rate or a decreasing temperature. Finally, the dynamic compressive stress–strain models for S30408 ASS under 20–600 °C were suggested on the basis of the Johnson-Cook (J-C) model and have been proved to give a reasonable prediction.